When Crime Tears Communities Apart: Social Capital and Organised Crime - Francesca Maria Calamunci; Federico Fabio Frattini (Fondazione Eni Enrico Mattei (FEEM), 2023)
What is the long-term effect of organised crime presence on social capital accumulation? By leveraging novel social capital and organised crime data, this study investigates this question within the Italian landscape. In an instrumental variable (IV) setting, we exploit the forced resettlement law that compelled organised crime members living in the South of Italy to resettle in the Centre-North area. Using a granular measure of tax compliance as a proxy for civic awareness, we find evidence that sustained exposure to mafia presence depresses social capital accumulation. This finding applies to other dimensions of social capital, such as civic engagement and political participation. Results are robust to a series of robustness checks, such as the alternative strategy which combines the migratory movements from the South and the allocation of Marshall Plan funds. The findings appear to be influenced by a tolerance of dishonest conduct, a decrease in institutional trust, and a general disengagement from social activities.
Keywords: A13; J16; K4; N34; O15; 330; Organised Crime; Social Capital; Forced Resettlement; Expansion